Estudos químicos e farmacológicos da Lippia gracilis Schauer - Mendes, Sandra Santos (2012)
Lippia genus has a great pharmacological and therapeutic potential and encompasses approximately 200 species of herbs, bushes and small trees with a consistent chemical composition and pharmacological, therapeutics and culinary activities. This research aimed to evaluate the chemical and pharmacological aspects of Lippia gracilis Schauer (Verbenaceae), well-known as alecrim do campo , which grew at the germplasm bank of the Federal University of Sergipe, Brazil. This study was divided in two parts: in the first one we tried to evaluate the nonpolar compounds from the essential oil (EO) of L. gracilis plants under hydric stress and without hydric stress. The identification of the EO was made by using GC/MS and its anti-inflammatory and antinociceptive activities were studied in animal models. As results, thymol, p-cineme, methyl thymol, and carvacrol were found in the EO analysis, independent of the hydric stress L. gracilis leaves were submitted. Although the different hydric stresses the plants pass through, the chemical composition of the EO was too similar, so it was chosen to study the one obtained from the plants submitted to hydric stress in the animal models. In the animal models, we fed 1 hour before the beginning of the experiments with the EO (50, 100, and 200 mg/kg, p.o.), vehicle (tween 80 at 0.2% in saline, 10 mL/kg, p.o.) and acetylsalicylic acid (ASA, 300 mg/kg, p.o.) or dexamethasone (Dexa, 2 mg/kg, s.c.). To evaluate the anti-inflammatory activity, we used paw oedema model (Wistar rats, 120- 180 g) and leukocyte migration into the peritoneal cavity (Swiss mice, 20-30 g). To evaluate the antinociceptive activity, we used acetic acid-induced abdominal writhes model in Swiss mice. In all in vivo experiments we used groups of 6 animals. In the paw oedema assay, could be verified a reduction in inflammation (p<0.01) at the 200 mg/kg dose in Wistar rats in all measurement time (1, 2, 3 and 4 hours after carrageenaninduced paw oedema). The positive control (AAS 300 mg/kg) was also able to reduce the inflammation (p<0.05). In the leucocyte migration model, all EO doses used (50, 100, and 200 mg/kg) were able to reduces leucocytes migration, caused by carrageneen (p<0.01). Dexa was also able to reduce the migration (p<0.001). In the acetic acidinduced abdominal writhes model, all the doses reduced the nociception caused by acetic-acid, whereas the 200 mg/kg dose showed similar effects to ASS (p<0.001). In the second part of this study, the main polar compounds of L. gracilis were evaluated using antioxidant in vitro assays, namely ABTS (2,2 -azino-bis (3-ethylbenzothiazoline6- sulphonic acid), FRAP (Ferric Reducing Antioxidant Power) and DPPH (2,2-di(4- tertoctylphenyl)- 1-picrylhydrazyl), with trolox as reference antioxidant. The chemical composition of aqueous and ethanolic extracts was also evaluated by HPLC (High Performance Liquid Chromatography) and LCMS (Liquid Chromatography Mass spectrometry). Three major compounds with high antioxidant activity could be identified: luteolin-C-6-glucoside, luteolin-C-8-glucoside and carvacrol. The antioxidant activity of the ethanolic extract was higher than the water extract (about 40%), independent of the solvent used. These three compounds were also tested isolate, besides their comparison with well-known antioxidants as quercetin and luteolin. The antioxidant activity clearly depends on the assay used and the compound structure. Carvacrol showed higher activity in ABTS assay than C-6 and C-8-glucosides, but lower in DPPH and FRAP assays. In all assays, luteolin-C-6 showed higher antioxidant activity than luteolin-C-8-glucoside. L. gracilis is a good source of compounds with potential antioxidant, anti-inflammatory and antinociceptive activities. This is the first time that luteolin C-6 and C-8-glucosides were described in the L. gracilis.